Energetics of swimming: a historical perspective - Zamparo, P.; Capelli, C.; Pendergast, D. (European Journal of Applied Physiology, 2011)
The energy cost to swim a unit distance (Csw) is given by the ratio E./v where E. is the net metabolic power and v is the swimming speed. The contribution of the aerobic and anaerobic energy sources to E. in swimming competitions is independent of swimming style, gender or skill and depends essentially upon the duration of the exercise. Csw is essentially determined by the hydrodynamic resistance (Wd): the higher Wd the higher Csw; and by the propelling effciency (gP): the higher gP the lower Csw. Hence, all factors influencing Wd and/or etaP result in proportional changes in Csw. Maximal metabolic power (E.max) and Csw are the main determinants of swimming performance; an improvement in a subject`s best performance time can more easily be obtained by a reduction of Csw rather than by an (equal) increase in Emax (in either of its components, aerobic or anaerobic). These sentences, which constitute a significant contribution to today`s knowledge about swimming energetics, are based on the studies that Professor Pietro Enrico di Prampero and his co-workers carried out since the1970s.This paper is devoted to examine how this body of work helped to improve our understanding of this fascinating mode of locomotion.